SURVEY OF IRRIGATION AREA USING MICRO UNMANNED AERIAL VEHICLE (MICRO-UAV) IN GUMBASA IRRIGATION AREA - Jabal Tarik Ibrahim; Nugroho Tri Waskitho; Wahono Wahono; Sitti Rahma Ma’mun (Socio-Economics/Agribusiness Department, 2017)
This study aims to develop a new approach in doing evaluation of irrigation system in terms of getting accurate data at a reasonable cost in an essay and fast manner. The research was done at Gumbasa Irrigation District in Sigi, Central of Sulawesi, Indonesia on May-June 2015. The workflow consists of: (i) preparation; (ii) flight planning; (iii) automated flight; (iv) data processing. Data analysis was done by comparison between Red Green Blue (RGB) method and Near Infra Red Green Blue (NirGB) method. The results show that the use of micro-UAV provide an efficient way to collect data needed to manage a very large irrigation system. The RGB image can be effectively used to identify crop’s condition on an irrigation area, which is needed to plan irrigation efficiently. The NirGB image can be effectively used to assess tertiary and secondary level of irrigation canal such as leakage.